Analisis Penerapan Akuntabilitas dan Transparansi Pengelolaan Dana Desa dalam Pembangunan Desa: (Studi Kasus Desa Tanjung Morawa-A Kabupaten Deli Serdang) - Aprilla Wardhahany Siregar; Nurlaila Harahap; Ahmad Syakir (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out how to implement accountability and transparency in managing village funds in village development in Tanjung Morawa-A Village. The method used in this research is a qualitative research method with a descriptive approach. The data collection technique used was interviews by interviewing village officials and documentation regarding budget realization reports. The results of this research show that the Tanjung Morawa-A village fund management mechanism includes planning, implementation, administration, reporting and accountability stages. The implementation of accountability in managing village funds in the development of Tanjung Morawa-A village has not been fully implemented in accordance with the regulations. This is proven in the management of village funds at the reporting and accountability stage in Tanjung Morawa-A Village, there are still obstacles, namely delays from village officials in submitting the APBDesa Realization Accountability Report to the center, the main cause of which lies in the inaccuracy of reports from the Activity Implementation Team (TPK) and conditions. Human resources are still limited. The implementation of transparency in the management of village funds in the development of Tanjung Morawa-A village is said to be not good, this is proven by the Tanjung Morawa-A Village government still not being open to the community regarding village financial information or not being transparent to the community regarding the management of village funds. Thus, the implementation of accountability and transparency in managing village funds in the development of Tanjung Morawa-A village is technically guided by Permendagri Number 20 of 2018, but its overall implementation is not yet fully in accordance with Permendagri Number 20 of 2018.